CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Question 6 (b)

From the sum of 4+3x and 54x+2x2, subtract the sum of 3x25x and x2+2x+5.


Solution

While adding or subtracting algebraic expressions we need to be aware that we can add/subtract only like terms.
Like terms have the same algebraic factors.
According to question,
(4+3x)+(54x+2x2)(3x25x) +(x2+2x+5)
=[4+3x+54x+2x2][3x25xx2+2x+5]
=[2x2+3x4x+5+4][3x2x2+2x5x+5]
=[2x2x+9][2x23x+5]
=2x2x+92x2+3x5
=2x22x2x+3x+95
=2x+4
So, the required expression is 2x+4.

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
View More...



footer-image